Academic English course for the health sciences: evolution towards a flipped classroom - Gudex, Claire; Pedersen, Jude; Kjær, Christopher (Tidsskriftet Læring og Medier (LOM), 2024)
The transition from university face-to-face teaching to blended learning can be challenging. This educational design research study investigated the optimal design for a blended and flipped learning approach to a scientific English course and the impact on student motivation and learning of incorporating pedagogical principles from adult and work-based learning. Using student feedback and teacher reflections, we evaluated three iterative cycles of development from trialling of e-modules in a face-to-face course, to a fully online course, to a blended learning approach with a flipped classroom. We found that student participants were increasingly satisfied over time and conclude that the final course design is the optimal approach for our context. Integrating principles of direct interest from adult learning and involvement of current work supported participant motivation, while self-paced e-modules allowed direct application of new knowledge. Coherence between pre-class, in-class, and post-class activities in the flipped classroom helped ensure relevant learning activities.